The Alps from End to End - Conway, William Martin (Cambridge University Press, 1895)
During a life of many and varied interests, the art historian and mountaineer William Martin Conway (1856-1927) served as a professor of art at Liverpool and Cambridge, a member of parliament, director-general of the Imperial War Museum, and president of the Alpine Club. He climbed extensively in Europe and the Himalayas, mapped part of the Karakoram range (for which he was knighted), and named several mountains. In 1894 he walked the length of the Alps accompanied by two Gurkha soldiers. The celebrated expedition took the party sixty-five days to complete. Conway and his companions climbed twenty-one peaks, including Mont Blanc, the Jungfrau and Grossglockner, and traversed thirty-nine mountain passes. Published a year later, this is the illustrated second edition of Conway's popular personal account of the expedition, in which he documents the party's progress on a daily basis.